2013
DOI: 10.9790/0853-0351520
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oral Administration of Artesunate on the Histology of the Kidney in Albino Rat.

Abstract: Abstract:The effect of oral administration of Artesunate on the histology of the Kidney of Albino Rat was determined histologically. Thirty Albino rats weighing 80-175g were divided into five groups (A-E) of five rats each. Group A (control) was give equal volume of distilled water daily. Group B received 4mg/kg/day of Artesunate for 5 days and were sacrificed on the 6th day. Group C were given 4mg/kg of Artesunate for the 1 st day, then 3mg/kg/day of Artesunate for 8 days and sacrificed on the 10 th day. Grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…As most drugs are excreted by the kidney, it is reasonable to assume that the kidney itself could be a privileged target of their toxic action [31]. Amaza et al [32] reported glomerulus degeneration and venous congestion after treatment with artesunate. It was hypothesized that the release of malaria antigens activates monocyte cells, to release proinflammatory cytokines and activate cellmediated response, causing renal problems [33].…”
Section: Discussionmentioning
confidence: 99%
“…As most drugs are excreted by the kidney, it is reasonable to assume that the kidney itself could be a privileged target of their toxic action [31]. Amaza et al [32] reported glomerulus degeneration and venous congestion after treatment with artesunate. It was hypothesized that the release of malaria antigens activates monocyte cells, to release proinflammatory cytokines and activate cellmediated response, causing renal problems [33].…”
Section: Discussionmentioning
confidence: 99%